2020
DOI: 10.1016/j.bbi.2020.04.074
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome as a complication of SARS-CoV-2 infection

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
106
0
6

Year Published

2020
2020
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 10 publications
1
106
0
6
Order By: Relevance
“…A total of 18 patients reported in 14 papers [12][13][14][15][16][17][18][19][20][21][22][23][24][25] were included in this review. The 14 selected papers consisted of 13 case reports and one series.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 18 patients reported in 14 papers [12][13][14][15][16][17][18][19][20][21][22][23][24][25] were included in this review. The 14 selected papers consisted of 13 case reports and one series.…”
Section: Study Selectionmentioning
confidence: 99%
“…Table 4 shows the diagnostic ancillary tests, outcome and treatment. Fourteen cases were from Europe [12,[16][17][18][19][20][22][23][24][25], one from the USA [13], one from China [14], one from Iran [15] and one from Morocco [21]. Ten patients were males whilst eight were females.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…GBS occurred in 5/1200 (0.4%) patients with COVID-19 in one of the studies [13]. There were six other case report of GBS, one Miller Fisher syndrome, and two polyneuritis cranialis [14,[24][25][26][27][28][29][30]. Interestingly, neurotropism of human coronaviruses has been suggested by in vitro and in vivo studies that showed that certain strains of the viruses could persist in the human CNS by targeting oligodendrocytic and neuroglial cell lines [41].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one patients experienced a cerebrovascular complication, with 27 ischemic strokes [11,[19][20][21][22][23], 3 hemorrhagic strokes [11,15,23] and 1 cerebral venous sinus thrombosis [11]. There were 15 patients with GBS [13,14,[24][25][26][27][28][29][30] or its variants, 6 reported as encephalitis [12,18,[31][32][33], one with seizures [34], one with acute hemorrhagic necrotizing encephalopathy [16] one reported as transverse myelitis [35], and one reported as ADEM [36]. Nine of these cases were reported as fatal.…”
mentioning
confidence: 99%